Effects of the COMT Val158Met polymorphism on N100 component of auditory evoked potential and oddball task performance in healthy subjects and schizophrenia patients - A. A. Fedotova; A. V. Kirenskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The study was conducted with the participation of 47 healthy subjects and 48 schizophrenia patients. The different effects of Val158Met polymorphism have been found in the control and patients groups. The increased N100 amplitude and minimal number of the error responses in oddball task were revealed in healthy subjects with Val/Val genotype. In patients group Val/Val genotype was related to the decreased N100 amplitude and worse performance of oddball task.